Wipe Sampling Method and Evaluation of Environmental Variables for Assessing Surface Contamination of 10 Antineoplastic Drugs by Liquid Chromatography/Tandem Mass Spectrometry. Issue 8 (3rd August 2017) - Colombo, Manuel; Jeronimo, Matthew; Astrakianakis, George; Apte, Chirag; Hon, Chun-Yip
Abstract: This paper describes a novel wipe sampling and high-performance liquid chromatography/tandem mass spectrometry (HPLC-MS/MS) method capable of simultaneously detecting 10 antineoplastic drugs (5-fluorouracil, oxaliplatin, methotrexate, vindesine, ifosfamide, cyclophosphamide, vincristine, vinblastine, docetaxel, and paclitaxel). The good overall recoveries and sensitivity values of this method along with the comparatively short run time (8 min) allows for its use in routine monitoring in health care facilities. The long-term behavior of the studied drugs on contaminated surfaces and the effect of surface roughness on drug recoveries were studied to gain insights about how these environmental variables influence the detection, cleaning, and occupational exposure of these drugs. Surfaces with higher roughness parameter ( R a ) values (rougher) had the lowest recoveries while those with lower R a (smoother) presented the highest recoveries. Long-term assessments evidence distinctive drug behaviors with oxaliplatin, vindesine, vincristine, and vinblastine being the less persistent drugs (~20% was recovered after 24 h) and docetaxel and paclitaxel the most persistent drugs with recoveries of 40% and 80% after 1 month. This information indicates the importance of collecting ancillary information about drug usage (throughput, timing, cleaning procedures, etc.) to interpret the results in the context of potential exposure. Finally, the method was successfully applied to evaluate trace surface contamination down to the single picogram per square centimeter in multiple work areas within three local health care centers on Vancouver Island, Canada.